The Role of Community Information Dissemination Centres in Community Development: A Case Study of Ebenezer Information Centre in Obogu in Asante-Akyem South Municipality - Obeng-Fosu, Kwasi (UniMAC-GIJ, 2021)
The study looked at how Community Information Dissemination Centres (CIDCs) help in enhancing community development. The study used qualitative approach to research. Interviews, discussion and observation were used to gather data. Purposive sampling was used to select the information centre that was studied. Purposive sampling was also used to select the respondents for the interviews. The study found out that information centres can be owned by one person or jointly owned. The study also found out that amplifier, desktop computer, microphone and horned-speakers make up the set-up of information centres. It was also found that information centres do announcement, promote health, agriculture and social issues. Again, it was found that information centres face power fluctuation challenges, low level of income for patronage and faulty equipment. Finally, the study recommends that government should regulate the use of information dissemination centres. Also, state institutions and other bodies should help train operators of information centres. Lastly, organizations should help set-up community information dissemination centres for information-poor communities in Ghana.
Thesis
Keywords: Community, Information Dissemination Centres, Community Development, Ebenezer Information Centre, Obogu, Asante-Akyem South Municipality